2013
DOI: 10.5539/mas.v7n6p26
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Solar Radiation as Encouraged to Produce an Increment of Dissolved Oxygen and Hydrogen Peroxide in Oxidation Ponds for Community Wastewater Treatment at H.M.The King’s LERD Project Site in Phetchaburi Province, Thailand

Abstract: H.M.The King's initiative nature by nature process for community wastewater treatment has been conducted since 1990 at Laem Phak Bia sub district, Ban Laem district, Phetchaburi province, Thailand on UTM 1442240 to 1443480 N and 0619271 to 0619271 E. The fresh food markets and households were the point sources of Phetchaburi municipal wastewater that flowing newly construction sewage system in order to receive them to four sub stations on both sides of Phetchaburi river before pumping to Klongyang collection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…H 2 O 2 is a powerful oxidant, which is produced as a by-product during the breakdown of superoxide by SODs, the first enzyme in the line of defense against oxidative stress [ 29 ]. Continuous production of H 2 O 2 will serve as an attractive means to bio-converse the solar radiation into storable chemical energy a special condition of its involvement in eliminating the toxicity [ 32 ]. It was well documented that cyanobacteria photoreduces O 2 with the concomitant formation of H 2 O 2 through the typical Mehler reaction [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 is a powerful oxidant, which is produced as a by-product during the breakdown of superoxide by SODs, the first enzyme in the line of defense against oxidative stress [ 29 ]. Continuous production of H 2 O 2 will serve as an attractive means to bio-converse the solar radiation into storable chemical energy a special condition of its involvement in eliminating the toxicity [ 32 ]. It was well documented that cyanobacteria photoreduces O 2 with the concomitant formation of H 2 O 2 through the typical Mehler reaction [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that increase in solar radiation increases dissolved oxygen content in the pond. Pattamapitoon et al (2013) showed that dissolved oxygen increase with radiation in a quadratic relationship. Sample B, E, K and M have higher values of dissolved oxygen because their reflectors reflected more radiation in the pond which increased the algal activities in the pond and subsequently increased dissolved oxygen content in the pond.…”
Section: Dissolved Oxygen (Do)mentioning
confidence: 99%
“…So, it has to point out that the sampling point at 30-cm depth is eligible for being representative of any depth while water in motion. Therefore, the water quality studies of streamflow in Phetchaburi river will be taken from only the 30-cm depth as shown in Table 3 and Figure 4 which is the international measuring depth (PCD, 2013; APHA, 1952; APHA.AWWA.WEF, 1992; Metcalf and Eddy, 1979;Ntengwe, 2006;Postel and Richter, 2003;Pattamapitoon, 2013;Reynolds and Edwards, 1995;Streeter and Phelps, 1958;Tanji et al, 2006;Vagnetti et al, 2003;Vargaftik et al, 1983;Wang et al, 1987).…”
Section: Variation Of Flow Rate On Measuring Water Depthmentioning
confidence: 99%
“…In addition, the stream length was influenced in the excessive contaminants owning to the efficiency of self purification in which the longer the distance is the more the recovery (Ntengwe, 2006;Vagnetti et al, 2003;Cazelles et al, 1991;Tanji et al, 2006;McColl, 1974;Liu & Chen, 2009;Kraus et al, 2014). In the same situation, if the bacterial digesting rate is less than organic wastes (both solid and liquid) releasing rate then the stream pollution may be caused the seriousness, especially the zones of dense populated in the riverine systems (Derx et al, 2014;Pattamapitoon, 2013;Vargaftik et al, 1983;Wang et al, 1978;Tyagi et al, 1999;Penha-Lopes et al, 2011;Srigate, 2009;Streeter & Phelps, 1958). …”
mentioning
confidence: 99%